Exploring Moral Values through Story Education: Madrasah Ibtidaiyah/Elementary School Student Character Building Solutions - Rita Sari; Sutrisno Sutrisno; Nina Rahayu; Febriyantika Wulandari; Taqwa Nur Ibad; Agus Riyan Oktori (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Learning Islamic values for Madrasah Ibtidaiyah (MI) students or Elementary School (SD) children presents challenges in conveying abstract moral and spiritual concepts, considering that children's cognitive abilities are at the concrete operational stage. The primary challenge is to effectively internalise Qur'anic values so that they can be understood, internalised, and practised in everyday life. This article aims to explore the effectiveness of learning based on Qur'anic stories as a pedagogical strategy that is appropriate to children's developmental characteristics. The research uses a qualitative approach with literature study methods. The results of the study show that Qur'anic stories have strong potential in forming noble morals, because they present characters, event plots, conflicts and resolutions that are concrete, so that it makes it easier for children to interpret abstract values. In addition, the integration of stories with creative methods such as role playing, drawing, and group discussions increases students' emotional engagement and conceptual understanding. This research recommends that MI/SD teachers develop interactive Qur'anic story-based learning models, use visual and audio media to strengthen the learning experience, and carry out ongoing assessments of the application of values in student behaviour. This approach is believed to be able to shape Islamic character from an early age and provide a strong foundation for the younger generation in facing the challenges of the times.